Business Distribution Model: Change or Not to Change? - Kafi, Abdul; Zainuddin, Nizamuddin; Mohd Yusoff, Yuhainis; Deraman, Norita (2023)
This teaching case revolves around a essential decision challenged by ABC Industry, a notable industry in the frozen food distribution sector. Amidst the ever-evolving market dynamics and shifting consumer preferences, the case provides into the considerations of the company regarding whether to reforme its existing distribution model or uphold the current process. As students engage themselves in the case, they analyze the intricate interplay of challenges and opportunities covering market trends, operational capabilities, competitive positioning, and financial implications. Their task involves evaluating the viability of a distribution model transformation. The case offers an array of perspectives from key stakeholders, senior management, marketing, operations, and finance. Students navigate through these diverse viewpoints to form a holistic comprehension of the decision-making landscape. By dissecting the company's ultimate choice, students gather insights into strategic decision-making, risk assessment, and alignment with long-term growth objectives. The case highlights the significance of adapting to emerging consumer behaviors while perceptively managing possible disruptions linked to a distribution model change. This illustration empowers students to significantly enhance their practical skills, furnishing them with a profound understanding to tackle distribution challenges and capitalize on opportunities in the ever-changing ABC industry.